Imerslund-Gräsbeck syndrome and generalized malabsorption - Yetgin, Sevgi; Özsoylu, Şinasi; Zamani, Vahide Prozorova (The Turkish Journal of Pediatrics, 1983)
A three-year-old patient with familial vitamin B12 malabsorption, or Imerslund-Gräsbeck syndrome, and growth retardation, was examined. Gastrointestinal studies showed that the patient had generalized malabsorption in addition to that of vitamin B12. The hematological findings, malabsorption and growth retardation of the patient returned to normal after vitamin B12 treatment. It is thought that the findings are the results of vitamin B12 deficiency. The combination of the Imerslund-Gräsbeck syndrome and generalized malabsorption suggest that an underlying defect is reinforced by vitamin B12 deficiency in these rare cases.
Keywords: familial Vit-B12 deficiency; Imerslund-Gräsbeck syndrome; megaloblastic anemia